Adopting the Concept of ‘Ba' and the ‘SECI' Model in Developing Person-Centered Practices in Child and Adolescent Mental Health Services - Attard, Christie; Elliot, Michelle; Grech, Paulann; McCormack, Brendan (Frontiers in Rehabilitation Sciences, 2022)
The concept of knowledge is divided into explicit and tacit knowledge; explicit knowledge refers to the knowledge that can be articulated, written and stored, while tacit knowledge refers to personal experiences, values, beliefs and emotions of an individual. By Nonaka's theory, explicit and tacit knowledge do not lie separately but interact together by interactions and relationships between human beings. Thus, the SECI model is based on the assumption that knowledge is created through the social interaction of tacit and explicit knowledge; known as knowledge conversion. The SECI model is based upon four modes of knowledge conversion; socialization, externalization, combination and internalization. 'Ba' is considered to be a shared platform for knowledge creation. 'Ba' is a shared space, be it physical, mental or a combination of both that serves as a foundation of knowledge creation. Ba involves sharing of tacit knowledge i.e. emotions, feelings, experiences and mental images. It also involves the formation of a collective relationship which is open to the sharing of practices, values, processes and culture. This concept focuses mainly on the individual as a person who holds the knowledge rather than just on the knowledge itself. It aims to create a common space to bring people together where they can dialogue to share and create knowledge. As in the relationships formed in person-centered practices, relationships formed in Ba are based on not just the sharing of objective knowledge but also on sharing values, beliefs, and emotions. It also reflects the formation of a person-centered environment as a basis for person-centered research where healthful relationships with the participants are formed. Furthermore, Ba will aid in creating a sense of connectiveness and dialogue, thus focusing on the idea that the development of new practices is done with others rather than to others. In this article we will discuss how these Eastern concepts can be adapted and used to develop person-centered practices within child and adolescent mental health services, specifically related to rehabilitation and recovery. The concepts of personhood will be discussed, followed by a reflection on current practices adopted when working with children and adolescents.